Khalaf Islamic Boarding School Education Pattern Based on the Value of Thobiat Luhur Character in Islamic Boarding Schools Nurul Huda Lampung - Abdul Azis Masthuri; Risma Margaretha Sinaga; Pujiati (International Journal of Educational and Life Sciences, 2024)
This study aims to find out the pattern of khalaf Islamic boarding school education based on the value of noble thobiat character, the impact of the implementation of character education based on noble thobiat and the strategies carried out by the Nurul Huda Lampung Islamic Boarding School in facing the development of the times related to the formation of student character. The data validity technique uses triangulation. The results of the study show that: 1) the pattern of khalaf pesantren education based on the value of noble thobiat character collaborates with formal schools that are integrated with the Nurul Huda Lampung Islamic Boarding School, namely junior high school, high school and vocational school Tri Sukses. The pattern of character development of students is carried out in stages which are divided into two categories, namely regular classes and intensive classes. Regular classes will receive general coaching, while intensive classes will receive special assistance. 2) The impact of this noble Thobiat character education is felt directly by the students. The student who became an informant said that there were many character changes in the good direction while studying at the boarding school. In addition to the students, the good impact is also felt by the surrounding community and even the surrounding community also practices noble thobiat in daily life. 3) The strategy carried out by the Nurul Huda Islamic Boarding School in facing the changing times is to always adapt. In addition to utilizing information technology, it also develops the independence of students.